Systematic reviews of research in basic education in South Africa - Maringe, Felix (SUN PReSS, 2021)
"This volume provides a useful foundation to the current state of education quality in South Africa including the impact of interventions. It also brings to the fore challenges still facing education transformation. The evidence presented which, taken together, lays out a coherent view of how improvements could be made."--Albert Chanee, Head of Planning, Gauteng Department of Education.